O papel do professor como mediador e gerenciador da co-construção das múltiplas leituras - Bárbara, Luciane de Alvarenga Santa (2007)
The National Curricular Parameters PCN (1997:57) - state that that reading is a kind of practice that should admit several readings . This multiplicity could be obtained by means of the interaction between a person and their social context (Vygotsky, 1984/1994), and the use of metaphors, tools which mediate thought and learning (Cameron, 2003). This research aimed at investigating how the practice of thinking aloud in group (Zanotto, 1995) in an activity of metaphor reading could contribute to the construction and negotiation of multiple readings in the classroom, comparing them to the reading suggested by the course book, and how, by analyzing my practice through action research, it is possible to orchestrate (O´Connor e Michaels, 1996) and mediate my students in a social reading event (Bloome, 1983). Within the area of Applied Linguistics focusing on education, this research, characterized as interpretive research (Moita-Lopes, 1994), was carried out with two groups of eighth graders in a state school. Tools used to collect data were a questionnaire, the thinking aloud in group technique (Zanotto, 1995) and a reflective diary (Machado, 1998). After the data had been analyzed, the results showed the richness of readings constructed by means of students interaction, the change on how they understood reading prior to the research, the role that metaphor plays as learning facilitator and the importance of reflection for the life of teachers who will no longer be the sole knower, but the mediator, will no longer see the student as an empty recipient, but as an agent in meaning construction